Crossover in Membranes for Aqueous Soluble Organic Redox Flow Batteries. Issue 12 (1st January 2019) - Small, Leo J.; Pratt, Harry D.; Anderson, Travis M.
Abstract : The performances of five commercial anion exchange membranes are compared in aqueous soluble organic redox flow batteries (RFBs) containing the TEMPO and methyl viologen (MV) redox pair. Capacities between RFBs with different membranes are found to vary by >50% of theoretical after 100 cycles. This capacity loss is attributed to crossover of TEMPO and MV across the membrane and is dominated by either diffusion, migration, or electroosmotic drag, depending on the membrane. Counterintuitively, the worst performing membranes display the lowest diffusion coefficients for TEMPO and MV, instead seeing high crossover fluxes due to electroosmotic drag. This trend is rationalized in terms of the ion exchange capacity and water content of these membranes. Decreasing these values in an effort to minimize diffusion of the redox-active species while the RFB rests can inadvertently exacerbate conditions for electroosmotic drag when the RFB operates. Using fundamental membrane properties, it is demonstrated that the relative magnitude of crossover and capacity loss during RFB operation may be understood.